Respectus Philologicus, 2010 Nr. 17 (22) - Bankauskaitė, Gabija (Respectus Philologicus, 2010)
CONTENTS I. PROBLEMS AND SOLUTIONS Jurga Cibulskienė (Lithuania). Are Ideologies Reflected in Metaphors?...11 Lara N. Sinelnikova (Russia). The Addresser as an Alter Ego of the Addressee...26 II. FACTS AND REFLECTIONS Oleg N. Grinbaum (Russia). Chapter 3 in Pushkin’s Novel Eugene Onegin: Rhythm and Sense in Tatiana Larina’s Letter ... 43 Jadvyga Krūminienė (Lithuania). Oscar Milosz as Translator: Playing Games with Memory... 55 Magdalena Ożarska (Poland). 19th-Century Lake District as a Land of Tourists, Homemakers and Writers: a Selection of Writings by Dorothy Wordsworth, William Wordsworth and Harriet Martineau... 67 Inga Bartkuvienė (Lithuania). Definitions of Nationality in the Theory of Homi K. Bhabha...79 Mindaugas Grigaitis (Lithuania). Deconstruction of Jaques Derrida: Theoretical Postulates and Possibilities of Practice... 94 Janusz Detka (Poland). Eastern Episode in Polish Poetry of 1955–1957... 106 Kristina Bačiulienė (Lithuania). The Worldview of Marcelijus Martinaitis’ Collection of Poems K. B. Suspect... 120 Yelena A. Nakhimova (Russia). Metaphorical Projection and Conceptual Integration in Political Communication... 130 Anna Biyumena (Belarus). Verbs of Period and Existence in Political Discourse... 139 Anna V. Vladimirova, Tatyana G. Skrebtsova (Russia). Discourse Strategies in Women and Men’s Glossies as a Reflection of Gender-Specific Behaviour... 148 Joanna Bryła (Poland). Phraseological Units in Fashion Advertisements...159 Michael Louis Bakalinsky (Ukraine). New Theory and Methodology of Social Dialect Studies: US Underworld Social Dialect as a Case in Point... 170 Tatiana V. Poplavskaia, Tatiana I. Svistun (Belarus). The Interrelation between Types and Functions Abbreviations Perform in the Internet-Discourse... 186 Vilhelmina Vitkauskienė (Lithuania). Review of Research Methods on Language E-Learning Interactions ...195 Bernd Gliwa (Latvia), Daiva Šeškauskaitė (Lithuania). What Does Dievmedis (God’s Tree) Have in Common with God(s)?...205 III. OPINION Olga Jagintseva (Estonia). The Ethnolinguistic and Etymological Aspects of the Noun Glyok ‘an Earthenware Jug’ ... 219 IV. OUR TRANSLATIONS Patrick Seriot (Switzerland). Oxymoran or Misundersanding. Anna Wierzbicka’s Universal Relativism of Natural Semantic Metalanguage. Part II. Translated by Vilhelmina Vitkauskienė... 227 V. SCIENTIFIC LIFE CHRONICLE Books reviews Saulius Lapinskas (Lithuania). MELNIKIENĖ, Danguolė, 2009. Dvikalbiai žodynai Lietuvoje: megastruktūros, makrostruktūros ir mikrostrutūros ypatumai... 233 Eleonora Lassan (Lithuania). ЛАРИНА, Татьяна, 2009. Категория вежливости и стиль коммуникации. Сопоставление английских и русских лингвокультурных традиций... 237 Galina Michailova (Lithuania). ЧЕРНЫХ, В. А., 2008. Летопись жизни и творчества Анны Ахматовой. 1889–1966... 241 Barbarа Greszczuk (Poland). LUCIŃSKI, Kazimierz, 2009. Языковые заимствования и ментальность... 247 Announce ... 249 VI. REQUIREMENTS FOR PUBLICATION... 250 VII. OUR AUTHORS... 258